Green Biobatteries: Hybrid Paper–Polymer Microbial Fuel Cells. (28th June 2018) - Mohammadifar, Maedeh; Yazgan, Idris; Zhang, Jing; Kariuki, Victor; Sadik, Omowunmi A.; Choi, Seokheun
Abstract: Paper‐based electronics have recently emerged as a simple, biodegradable, and low‐cost paradigm for disposable electronics and may be an excellent way to reduce the dramatic increase in electronic waste. Paper‐based batteries are imperative for stand‐alone and self‐sustained paper‐based electronics. Ideally, paper‐based batteries must be simple, biodegradable, inexpensive, and provide realistic and accessible power. Among many paper‐based batteries, paper‐based microbial biobatteries attract significant attention because of their self‐sustainability, cost‐effectiveness, eco‐friendliness, and potential for energy accessibility in resource‐constrained settings. However, the promise of this technology has not translated into practical power applications because of its low performance. Furthermore, its biodegradability remains questionable. In this work, an easily biodegradable paper‐polymer substrate is engineered as a part of a novel, high‐performance microbial battery. Poly (amic) acid and poly(pyromellitic dianhydride‐p‐phenylenediamine) are processed and incorporated into a porous, hydrophilic network of intertwined cellulose fibers to revolutionize oxygen‐blocking, proton‐exchanging, and biodegrading properties of the paper‐based microbial biobatteries, which ultimately offer the transformative potential of "green" electronics. Furthermore, the battery, formed by adding engineered polymers to the paper, exhibits a much higher power‐to‐cost ratio than all previously reported paper‐based microbial batteries. The biobattery clearly biodegrades without the requirements of special facilities, conditions, or introduction of other microorganisms. Abstract : An easily biodegradable paper–polymer substrate is engineered as part of a novel, high‐performance microbial battery. Poly (amic) acid and poly(pyromellitic dianhydride‐ p ‐phenylenediamine) are processed and incorporated into a porous, hydrophilic network of intertwined cellulose fibers to revolutionize oxygen‐blocking, proton‐exchanging, and biodegrading properties of the paper‐based microbial biobatteries, which ultimately offer the transformative potential of "green" electronics.